Betweenness in graphs: A short survey on shortest and induced path betweenness. Issue 1 (1st April 2019) - Changat, Manoj; Narasimha-Shenoi, Prasanth G.; Seethakuttyamma, Geetha
Abstract: Betweenness is a universal notion present in several disciplines of mathematics. The notion of betweenness has a profound history and many pioneers like Euclid, Pasch, Hilbert have studied betweenness axiomatically. In discrete mathematics too, betweenness is present and several authors have worked on this concept from an axiomatic view. In graph theory, betweenness is developed mainly as metric betweenness, studied using the shortest path metric in a connected graph, thus resulting in the notion of the interval function. Many interesting results are available in graph theory using the interval function. The interval function is generalized to induced path function by replacing shortest paths by induced paths. The induced path betweenness also captured attention among graph theorists with several interesting results to date. From an axiomatic point of view, two pertinent questions can be framed on these functions. Is it possible to axiomatically characterize the interval function of some special graphs using some set of first order axioms defined on an arbitrary transit function? Is it possible to characterize the graphs with the help of their interval functions? In this paper, we survey the results as answers to these questions available from the research papers.